Altered tissue specialized pro-resolving mediators in chronic rhinosinusitis. (January 2021) - Vickery, Thad W.; Armstrong, Michael; Kofonow, Jennifer M.; Robertson, Charles E.; Kroehl, Miranda E.; Reisdorph, Nichole A.; Ramakrishnan, Vijay R.; Frank, Daniel N.
Highlights: Distinct lipidomic signatures in CRS offer new therapeutic targets for each subtype. Pro-resolving mediators RvD2 and LXA4 are elevated in CRSwNP compared to CRSsNP. Sinonasal RVD1 and RvD2 are decreased in cigarette smokers compared with never-smokers. Upper airway microbiota are associated with lipid mediators in underlying tissue. Abstract: Current literature implicates arachidonic acid-derived leukotrienes and prostaglandins in the pathogenesis of chronic rhinosinusitis. However, other omega-3 and omega-6 derived lipid mediators, such as specialized pro-resolving mediators (SPMs), may also be important in chronic inflammatory disorders of the upper airway. We hypothesize that SPMs differ among CRS subtypes compared to controls and in relation to sinonasal microbiota. Ethmoid sinus tissue and middle meatal swabs were collected from a convenience sample of 66 subjects, including non-CRS controls, CRS with polyps (CRSwNP), and CRS without polyps (CRSsNP). Lipid mediator pathways were analyzed by liquid chromatography/tandem mass spectrometry. Bacterial taxa were profiled in parallel by 16S rRNA gene sequencing. Resolvin D2 was elevated in both CRSwNP ( p = 0.00076) and CRSsNP ( p = 0.030) compared with non-CRS controls. Lipoxin A4 was significantly increased in CRSwNP compared with CRSsNP ( p = 0.000033) and controls ( p = 0.044). Cigarette smoking was associated with significantly lower concentrations of several 15-lipoxygenase metabolites including resolvin D1 ( p = 0.0091) and resolvin D2 ( p = 0.0097), compared with never-smokers. Several of the lipid compounds also correlated with components of the sinonasal mucosal microbiota, including bacterial pathogens such as Pseudomonas aeruginosa . These data suggest that dysfunctional lipid mediator pathways in CRS extend beyond the traditional descriptions of leukotrienes and prostaglandins and include SPMs. Furthermore, dysregulated SPM signaling may contribute to persistent inflammation and bacterial colonization in CRS.